Adaptive optics for vision science : (Wiley-Interscience, 2006)
Although the book is written primarily for researchers in vision science and ophthalmology, the field of adaptive optics has strong roots in astronomy. Researchers in both fields share this technology and, for this reason, the book includes chapters by both astronomers and vision scientists. Following the introduction, chapters are divided into the following sections: Wavefront Measurement and Correction; Retinal Imaging Applications; Vision Correction Applications; Design Examples.